СОСТОЯНИЕ АКАДЕМИЧЕСКОЙ НАУКИ КАРАКАЛПАКСТАНА НА НАЧАЛЬНОМ ЭТАПЕ НАЦИОНАЛЬНОЙ НЕЗАВИСИМОСТИ - Сеилбекова, Р. (SCIENCE and SOCIETY, 2023)
This article is about the development of science and its main directions in the first years of independence, as well there is given information as about the activities of scientific research institutes.